1960
DOI: 10.1039/jr9600001390
|View full text |Cite
|
Sign up to set email alerts
|

277. Syntheses of poly-S-alkyl-L-cysteines

Abstract: Various S-alkylcysteine derivatives have been prepared and polymerisedProperties of the by various methods through their N-carboxy-anhydrides. amino-acids and their polymers are reported. SOME S-alkylcysteine derivatives have been found to occur in Nature. isolated S-allyl-L-cysteine S-oxide ( a h ) from garlic. S-Methylcysteine S-oxide has been found in various plants; the deoxo-compound was enzymically synthesised from serine and methanethiol and has been suggested as an intermediate in the microbial biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The preparation of samples for SDS/PAGE and the conditions for SDS/PAGE and actin immunoblots are as described (13). Western transfer of gels containing the myosin tail fragment was performed as described (14); these blots were probed with monoclonal antibody 4A1519 (kindly provided by Helen Blau, Stanford University, Stanford, CA) and visualized using goat antirabbit horseradish peroxidase conjugate (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of samples for SDS/PAGE and the conditions for SDS/PAGE and actin immunoblots are as described (13). Western transfer of gels containing the myosin tail fragment was performed as described (14); these blots were probed with monoclonal antibody 4A1519 (kindly provided by Helen Blau, Stanford University, Stanford, CA) and visualized using goat antirabbit horseradish peroxidase conjugate (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Dictyostelium cells have been used as host cells for genetic manipulation of contractile and cytoskeletal proteins such as myosin (14,15) and a-actinin (16). Although it has been reported that actin expressed in Escherichia coli can be purified as a functional protein after detergent treatment (17), we preferred using Dictyostelium cells to express recombinant actins because an easier and milder purification procedure is possible for the latter system.…”
mentioning
confidence: 99%
“…Attempts to express actin in Escherichia coli resulted in insoluble aggregates due to the lack of the required cytosolic chaperonin containing TCP-1 in prokaryotes (10,reviewed in Ref. 11).…”
mentioning
confidence: 99%